Effect of Public Infrastructure Investment on Local Residents in Johannesburg, South Africa - Makalima, Mzuchumile (Acta Carolus Robertus, 2022)
Infrastructure investment is one of the most important prerequisites for poor nations to accelerate or sustain their development and meet the Millennium Development Goals (MDGs) established by the United Nations in 2000. Furthermore, Johannesburg’s future infrastructure investment demands considerably outnumber the amount invested by the government, the private sector, and other stakeholders, resulting in a large financial imbalance. Johannesburg’s government, through Johannesburg’s National Treasury, has set in motion infrastructure-investment programs aimed to continue establishing numerous economic and social infrastructure programs to boost economic growth and job creation in Johannesburg. These programs include the RDP and NGP 320 participants were used in the research survey of this study. 160 participants, which are a total of 50% of the sample were selected from two neighborhoods in the suburban area of Sandton City, an affluent urban section in Johannesburg, and the rest of the 50% was sampled from Alexandra, the poorest neighborhood in Johannesburg. Ultimately, the Literature reviewed by this study suggests that a strong and directly proportional relationship exists between investments in infrastructure by countries of all statutes, specifically Johannesburg. This study’s primary research agrees with the literature on this subject as it also suggests that infrastructure investment is a key component of stimulating economic activity and ultimately improving people’s livelihoods